2019
DOI: 10.5194/amt-12-5593-2019
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of column NO<sub>2</sub> amounts from the OMI satellite compared to diurnally varying ground-based retrievals from multiple PANDORA spectrometer instruments

Abstract: Abstract. Retrievals of total column NO2 (TCNO2) are compared for 14 sites from the Ozone Measuring Instrument (OMI using OMNO2-NASA v3.1) on the AURA satellite and from multiple ground-based PANDORA spectrometer instruments making direct-sun measurements. While OMI accurately provides the daily global distribution of retrieved TCNO2, OMI almost always underestimates the local amount of TCNO2 by 50 % to 100 % in polluted areas, while occasionally the daily OMI value exceeds that measured by PANDORA at very cle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 47 publications
7
47
0
Order By: Relevance
“…Several studies have discussed in detail the impact of algorithmic differences on the NO2 column uncertainty, which can reach 42%, mainly due to tropospheric AMF uncertainties (Lorente et al, 2017). The underestimation of the NO2 satellite products identified here at a large number of stations, confirms what was 5 obtained in previous validation exercises using fewer sites and different satellite products (Celarier et al, 2008;Brinksma et al, 2008;Vlemmix et al, 2010;Irie et al, 2008;Lin et al, 2014;Halla et al, 2011;Irie et al 2012;Shaiganfar et al, 2011;Ma et al, 2013;Kanaya et al, 2014;Wang et al 2017b;Mendolia et al 2013;Tzortziou et al, 2014;Lamsal et al, 2014;Drosoglou et al, 2017;Herman et al, 2019;Judd et al, 2019;Compernolle et al 2020). These studies generally reported small negative or positive biases over rural (unpolluted) measurement sites 10 and stronger (systematic) negative biases over urban polluted sites.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Several studies have discussed in detail the impact of algorithmic differences on the NO2 column uncertainty, which can reach 42%, mainly due to tropospheric AMF uncertainties (Lorente et al, 2017). The underestimation of the NO2 satellite products identified here at a large number of stations, confirms what was 5 obtained in previous validation exercises using fewer sites and different satellite products (Celarier et al, 2008;Brinksma et al, 2008;Vlemmix et al, 2010;Irie et al, 2008;Lin et al, 2014;Halla et al, 2011;Irie et al 2012;Shaiganfar et al, 2011;Ma et al, 2013;Kanaya et al, 2014;Wang et al 2017b;Mendolia et al 2013;Tzortziou et al, 2014;Lamsal et al, 2014;Drosoglou et al, 2017;Herman et al, 2019;Judd et al, 2019;Compernolle et al 2020). These studies generally reported small negative or positive biases over rural (unpolluted) measurement sites 10 and stronger (systematic) negative biases over urban polluted sites.…”
supporting
confidence: 81%
“…BIRA-IASB MAX-DOAS stations have been regularly used for the validation of GOME-2 GDP products from MetOp-A and MetOp-B (Valks et al, 2011;Pinardi et al, 2011;Liu et al, 2019b) as part of the AC SAF activities (Hassinnen et al, 2016; see also www.cdop.aeronomie.be/validation/validresults). Pandora datasets have also been used in satellite validation of total and tropospheric NO2 columns (Herman et al 2009;Tzortziou et al, 2014;Judd et al, 2019) and a recent study of Herman et al (2019) 35 presented an overview at 14 Pandora sites showing that NASA OMI NO2 overpass data consistently underestimate the Pandora derived NO2 amounts. One general conclusion of these exercises was to find a low bias of the satellites tropospheric NO2 columns in urban conditions and, in contrast, a better agreement with ground-based data in background and pristine locations (Celarier et al, 2008;Halla et al, 2011;Kanaya et al, 2014).…”
mentioning
confidence: 99%
“…One of its primary data products is NO 2 total vertical column density (VCD total ) from the directsun viewing mode, where VCD total represents the vertically integrated number of molecules per unit area and is reported in units of molec cm −2 or Dobson units (1 DU = 2.6870 × 10 16 molec cm −2 ). The Pandora direct-sun NO 2 VCD total products have been validated through many field campaigns (Flynn et al, 2014;Lamsal et al, 2017;Martins et al, 2016;Piters et al, 2012;Reed et al, 2015) and ground-based comparisons (Herman et al, 2009;Wang et al, 2010) and used in satellite validations (Griffin et al, 2019;Herman et al, 2019;Ialongo et al, 2016Ialongo et al, , 2020Lamsal et al, 2014). Since their introduction in 2006, Pandora spectrometers have been deployed at more than 50 sites globally.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have related Pandora measurements to in situ, surface measurements (Flynn et al 2014, Knepp et al 2015, Kollonige et al 2018, and a few have explicitly examined diurnal variability. The most thorough examination of diurnal variability to date has been presented by Herman et al (2019), who find significant time-of-day structure in the NO 2 columns, with patterns differing by location, season, and individual days.…”
Section: Reconciling Surface and Column No 2 Variabilitymentioning
confidence: 99%